Sexualwesen Mensch : Texte zur Erforschung der Sexualität - Kentler, Helmut 1928-2008 Hrsg (Hoffmann und Campe, 1984)
Helmut Kentler: "Sexualwesen Mensch - Texte zur Erforschung der Sexualität". Hoffmann u. Campe Verlag, Hamburg 1984. 359 S., br., 36,- DM